An Analysis of 'Urf on the Practice of Jeluk-Jelukan in the Customary Marriages in Sambungmacan Village, Sragen Regency - Lukluk Uljanah (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2025)
Marriage is an order given by Allah to His servants which aims to create a family that is sakinah mawadah warahmah, so that Allah gives extraordinary gifts and rewards to the perpetrators. Marriage for Javanese people is something sacred and considered very important because the implementation of marriage is full of rituals which, when examined, have many meanings that can be interpreted as a manifestation of prayer so that the bride and groom and also their families get good things and away from disasters. In the customary law of Sambungmacan Village, marriage procedures are a combination of customary and Islamic law. According to local beliefs, if a person who wants to get married still has an older sibling who has not been married, it is very prone to disasters such as difficulty getting a mate for those who are stepped over, crazy, or kuwalat for the prospective bride and groom who step over. For this reason, the existence of this custom can prevent these disasters. The phenomenon that occurs in the Sambungamcan Village community if the younger sibling marries before the older sibling, then the older sibling is required to carry out the jeluk-jelukan tradition. This article aims to uncover the phenomenon of how 'urf and Islamic law review the jeluk-jelukan tradition that develops in the Sambungmacan Village community. This type of research is prescriptive field research, while the approach used is a legal normative approach, which is a problem approach by formulating whether something is or the object of research is good or should not be done so that it is in accordance with Islamic Law or not. The conclusion of this research is. This jeluk-jelukan tradition is classified as 'urf fasid, because it overturns the Islamic faith when believing that the calamity comes because of violating or not carrying out the jeluk-jelukan tradition. When viewed from the perspective of 'urf, it cannot be used as a basis or legal basis. In the review of Islamic law, this jeluk-jelukan marriage is contrary to Islamic law because the pillars of marriage are not fulfilled, namely without the guardian of the old widow. So it can be concluded that this jeluk-jelukan marriage is invalid. Because both of them are forced by customary law